APPLICATION OF Eco-Enzyme CONVERSION RESULTS INTO DISHWASHER SOAP - Tedang, Bybyani; Roring, Verawati Ida Yani; Moko, Emma Mauren; Posumah, Danny Christian; Lawalata, Helen J (Universitas Negeri Manado, 2024)
The application of the conversion results from Eco-Enzyme into dishwashing soap, the fermentation process lasts for one months, where the resulting liquid is dark brown in color and has a very strong sweet and sour fermented aroma. There is a lack of public knowledge about the very profitable benefits of Eco-Enzyme, such as as a multi-purpose cleaner as a multi-functional liquid which can be converted, one of the ways, into dishwashing soap. This research aims to determine the application of the results of converting Eco-Enzyme into dishwashing soap. This research used experimental methods and a research period of 3 months. This Eco-Enzyme is made with a ratio of organic ingredients: sugar: water 3:1:10. The Eco-Enzyme harvest is converted into dishwashing soap by adding lerak and Methyl Ester Sulfonate (MES). Eco-Enzyme conversion soap was then applied to several treatment groups: plastic plates, cans and glass. The results of the application show that the dishes washed with Eco-Enzyme using lerak have not completely removed dirt, oil and odors in each treatment, whereas Eco-Enzyme using Methyl Ester Sulfonate (MES) when compared with Sunlight brand liquid soap sold on the market shows that there are similarities both in terms of cleanliness, tapestry and smell. The research conclusion is that the application of the Eco-Enzyme conversion results has significant potential to be developed into an active ingredient for environmentally friendly dishwashing soap.